The Effect of Dosage and Type of Fertilizer on the Percentage of attacks of Brown Planthopper (Nilaparvata lugens stall.) on some Varieties of Paddy (Oryza Sativa L.) - Arkhiadi Benauli (Journal of Biodiversity and Biotechnology, 2022)
The effect of dosage anf type of fertilizer on the percentage of attacks of brown planthopper (Nilaparvata lugens Stall.) on Some Varieties of Paddy (Oryza sativa L.). This study aims to determine the dose of cow manure on the percentage of brown plant hopper attack  in several varieties of paddy. This research was conducted in Desa Serdang in March-June 2021. This research used Randomized Block Design (RAK) of two factors and three replications. The first factor  is fertilizer dose consisting of 4 treatments (anorganic, 50 kg / plot, 100 kg / plot and 150 kg / plot). The other factor  is a variety consisting of 2 treatments (Inpari 10 and Inpari 32). The results showed that the dosage of 100 kg / plot cow manure was the best treatment to production per plot and resistant to the pecentage of brown plant hopper attack. Inpari 32 is the best treatment to increase production per plot and resistant to the intensity of brown plant hopper attack. The interaction of fertilizer dosage and variety (Inpari 32 + 100 kg / plot) is the best treatment to increase production per plot and resistant to the percentage of brown plant hopper attack.